2018
DOI: 10.1007/s13300-018-0508-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D and Parathyroid Hormone with Insulin Sensitivity, Beta Cell Function and Gestational Diabetes in Pregnancy: A Cross-Sectional, Observational Study

Abstract: IntroductionVitamin D (25OHD) and parathyroid hormone (PTH) are associated with dysglycemia, and we investigated them in gestational diabetes mellitus (GDM).MethodsIn this cross-sectional, observational study, we included 75 pregnant women between 24 and 28 weeks of gestation. A fasting venous sample was collected for plasma glucose (FPG), insulin, PTH and 25OHD. Glucose and insulin samples were collected hourly after 75 g glucose load for 2 h. Insulin sensitivity was estimated by the Matsuda index (MI) and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Same direction was observed for mean of FBS , while ameliorate 25(OH)D levels (sufficient group) in women with GDM normalizes FBS (8) . Our study agrees with Amit et al 2018 as he showed an equal prevalence of 25(OH)D defeciency in women with and without GDM (25) . Different observations have been presented in Zuhur et al 2013 which exhibited that GDM is linked with only severe 25(OH)D defeciency but the exposure of sun the differently , the population of study , types of diet , measurement and clarify of 25(OH) D deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Same direction was observed for mean of FBS , while ameliorate 25(OH)D levels (sufficient group) in women with GDM normalizes FBS (8) . Our study agrees with Amit et al 2018 as he showed an equal prevalence of 25(OH)D defeciency in women with and without GDM (25) . Different observations have been presented in Zuhur et al 2013 which exhibited that GDM is linked with only severe 25(OH)D defeciency but the exposure of sun the differently , the population of study , types of diet , measurement and clarify of 25(OH) D deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Increased serum concentrations of PTH were found in diabetics (14). Nachakar et al found that increased PTH was associated with decreased insulin sensitivity, β-cell function and GDM during pregnancy, regardless of the underlying 25OHD level (37). In the present study PTH levels were not different in all groups.…”
Section: Discussionsupporting
confidence: 45%
“…Because PA patients did not receive PTH examination routinely, we could not get this data and analyze the relationship between PTH and DM. However, some studies did find that increased PTH was associated with decreased insulin sensitivity and pancreatic beta-cell function (36,37).…”
Section: Discussionmentioning
confidence: 99%